DEPOPULATION OF TRADITIONAL MINING REGIONS IN CENTRALAND EAST EUROPE: CASE STUDY OF THE UPPERSILESIAN BASIN (POLAND)AND THE DONETSK BASIN (UKRAINE) - Rechlowicz, Marcin; Tkocz, Maria (European Scientific Journal, ESJ, 2013)
The article compares demographic processes taking place in traditional industrial European regions: Upper-Silesian and the Donetsk Basins, which are in their declining stage of development. During communism, a high population concentration was characteristic, currently, migration and population decline are leading to depopulation. Depopulation in the Upper-Silesian Basin is determined mainly by labour migration to the European Union (EU) and by sub-urbanization, whereas, in the Donetsk Basin, it is due to severe population decline intensified by migration. The main reasons are poor economies of the regions, connected with the collapse of numerous industrial facilities and the lack of alternative employment.